ANALISIS PENGARUH TENAGA KERJA, EKSPOR DAN INFLASI TERHADAP PENANAMAN MODAL DALAM NEGERI (PMDN) KALIMANTAN TENGAH - Dadang Sudirman (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Mechanism of investment is an initial stage in production activity of a nation. Investment also is the initial stage in economic development activity. In the effort to develop the economy, each country always tries to create such a climate to be able to encourage investment. The targets are not only the community or private party in the country, but also foreign investment. The research aims to (a) analyze whether manpower influences on the PMDN in Central Kalimantan Province, (b) analyze whether export influences on the PMDN in Central Kalimantan Province, (c) analyze whether inflation influences on the PMDN in Central Kalimantan Province, (d) analyze whether dummy variable of ecoomic crisis influences on the PMDN in Central Kalimantan Province, (e) analyze whether the effects of man power, export, inflation, and dummy variable on the Domectic Investment in Central Kalimantan Province. The data used in this research is the secondary data obtained from Central Statistics Board and Annual Report of Bank Indonesia in various publication years. The data analysis was conducted by ordinary least square regression method, with function of domestic investment = f (Manpower, export, and inflation as well as dummy variable of economy).Results of the research are (a) The manpower provides positive effects on the Domestic Investment in Central Kalimantan Province.It means that the increase on manpower will increase on the Domestic Investment in Central Kalimantan Province. (b) Export provides positive effects on the Domestic Investment in Central Kalimantan Province. It means that the increase on export will increase on the Domestic Investment in Central Kalimantan Province. (c) The inflation provides positive effects on the Domestic Investment in Central Kalimantan Province.It means that the increase on inflation will increase on the Domestic Investment in Central Kalimantan Province. (d) The dummy variable of economic crisis provides negative and significant effects on the Domestic Investment in Central Kalimantan Province.It means that the economic crisis will decrease on the Domestic Investment in Central Kalimantan Province. (e) Results of the testing simultaneously show that the variables of manpower, export and inflation rate as well as dummy variable of economic crisis provide effects on the Domestic Investment in Central Kalimantan Province.Keywords: Capital Investment, Manpower, Export, Inflation.